Possibilities of using electrochemical technology for modifying properties and water quality control - Міхалєва, Марина Станіславівна; Світлик, Ірина Володимирівна (Technology audit and production reserves, 2014)
Using the measured value of the ox-redox potential in the regulation of production processes and product quality control is discussed in the paper. The main purpose of the research is to develop an electrical method and characteristics for rapid and objective evaluation of the quality of process fluids and finished products. With the development of experimental techniques and synthesis of the new chemical compounds, the possibility to develop electrical methods and techniques, which accelerate production processes, replace multistage laboratory studies and ensures accuracy and speed of obtaining the result, has appeared. The analysis of the results of experimental studies of model and real process multicomponent fluids is given in the paper. The dependences of the composition and the degree of oxidation of the liquid components on their consumer properties are obtained. The method for fast modification of fluid properties by means of the electrical action, which affect the production processes and the finished product quality, is proposed. The electrical characteristic of evaluating the quality of bottled natural drinking water is proposed. The paper may be of interest to experts in physical chemistry and metrology. The research results can be applied to fluid production diagnostics, finished products composition control, waste and environment monitoring in the food, pharmaceutical and other industries.